Kiekie, a new Neotropical spider genus of Ctenidae (Cteninae, Araneae) - Polotow, Daniele; Brescovit, Antonio D. (Zootaxa, 2018)
Kiekie gen. nov. is newly proposed to accommodate 11 Neotropical Ctenidae species. With the exception of one species from Colombia, they are all distributed in Central America. Two species are transferred from Ctenus: Kiekie sinuatipes (F.O. Pickard-Cambridge, 1897) comb. nov. from Costa Rica, and K. curvipes (Keyserling, 1881) comb. nov., with broader distribution from Mexico to Panama. Ctenus incolans (F.O. Pickard-Cambridge, 1900) is synonymized with Kiekie curvipes. Nine species are newly described. Kiekie garifuna sp. nov. was collected in Guatemala and Honduras. Four species were collected in Costa Rica: Kiekie sanjose sp. nov., K. verbena sp. nov., K. sarapiqui sp. nov., and K. griswoldi sp. nov.. Two species were collected in Panama: Kiekie barrocolorado sp. nov. and K. panamensis sp. nov.. Kiekie montanensis sp. nov. was collected in Costa Rica and Panama. Kiekie antioquia sp. nov., from Colombia, was the only species collected in South America. To support the description and further identification of the genus and its species, we provide illustrations of male and female genitalia, habitus and modified metatarsus of the male leg IV, measurements and diagnostic characters. We also provide a distributional map of the specimens herein recorded. Taxonomic changes are based in recent cladistics analysis, showing that at least two species belong to a well-supported clade, sister group of Africactenus Hyatt, 1954. We discuss the phylogenetic relationship of the group and the evolution of key morphological characters.